[18F]AV‐1451 clustering of entorhinal and cortical uptake in Alzheimer's disease. Issue 2 (6th February 2018) - Whitwell, Jennifer L.; Graff‐Radford, Jonathan; Tosakulwong, Nirubol; Weigand, Stephen D.; Machulda, Mary; Senjem, Matthew L.; Schwarz, Christopher G.; Spychalla, Anthony J.; Jones, David T.; Drubach, Daniel A.; Knopman, David S.; Boeve, Bradley F.; et al.
Abstract : Objective: To use a cluster analysis of [ 18 F]AV‐1451 tau‐PET data to determine how subjects with Alzheimer's disease (AD) vary in the relative involvement of the entorhinal cortex and neocortex, and determine whether relative involvement of these two regions can help explain variability in age and clinical phenotype in AD. Methods: We calculated [ 18 F]AV‐1451 uptake in entorhinal cortex and neocortex in 62 amyloid‐positive AD patients (39 typical and 23 atypical presentation). tau‐PET (positron emission tomography) values were normalized to the cerebellum to create standard uptake value ratios (SUVRs). tau‐PET SUVRs were log‐transformed and clustered blinded to clinical information into three groups using K‐median cluster analysis. Demographics, clinical phenotype, cognitive performance, and apolipoprotein e4 frequency were compared across clusters. Results: The cluster analysis identified a cluster with low entorhinal and cortical uptake (E Lo /C Lo ), one with low entorhinal but high cortical uptake (E Lo /C Hi ), and one with high cortical and entorhinal uptake (E Hi /C Hi ). Clinical phenotype differed across clusters, with typical AD most commonly observed in the E Lo /C Lo and E Hi /C Hi clusters, and atypical AD most commonly observed in the E Lo /C Hi cluster. The E Lo /C Lo cluster had an older age at PET and onset than the other clusters. Apolipoprotein e4 frequency was lower in the E Lo /C Hi cluster. The E Hi /C Hi cluster had the worst memory impairment, whereas the E Lo /C Hi cluster had the worst impairment in nonmemory domains. Interpretation: This study demonstrates considerable variability in [ 18 F]AV‐1451 tau‐PET uptake in AD, but shows that a straightforward clustering based on entorhinal and cortical uptake maps well onto age and clinical presentation in AD. Ann Neurol 2018 Ann Neurol 2018;83:248–257